Letter to Jane Tolmach from Roger Boas - Roger Boas:::::: (1971)
In this January 5, 1971 letter, State Chairman Roger Boas confirms his earlier telegram requesting that Jane Tolmach attend a January 9 meeting in Los Angeles to discuss all aspects of the upcoming Democratic State Central Committee convention. He emphasizes that, due to confusion over certain convention policies, her attendance is important.